2007
DOI: 10.1007/s00109-007-0159-4
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) is one of the leading causes of cancer death in China. In the present study, proteins in tumors and adjacent normal esophageal tissues from 41 patients with ESCC were extracted, and two-dimensional electrophoresis (2-DE) was performed using the pH 3-10 and 4-7 immobilized pH gradient strips. The protein spots expressed differentially between tumors and normal tissues were identified by matrix-assisted laser desorption/ionization and liquid chromatography electrospray/i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
93
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 44 publications
6
93
0
Order By: Relevance
“…CRT may have an important role in the development and/or progression of various human cancers: overexpression of CRT has been found in breast ductal carcinoma (Bini et al, 1997;Chahed et al, 2005), prostate adenocarcinoma (Alaiya et al, 2000), hepatocellular carcinoma (Kim et al, 2004) and colon cancer (Vougas et al, 2008). In ESCC, research by other groups and our previous finding suggests that CRT overexpression is a prevalent event in malignant transformation of esophageal epithelial cells (Nishimori et al, 2006;Du et al, 2007). Importantly, we observed that patients with CRT overexpression presented a shorter survival time compared to those with low CRT expression.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…CRT may have an important role in the development and/or progression of various human cancers: overexpression of CRT has been found in breast ductal carcinoma (Bini et al, 1997;Chahed et al, 2005), prostate adenocarcinoma (Alaiya et al, 2000), hepatocellular carcinoma (Kim et al, 2004) and colon cancer (Vougas et al, 2008). In ESCC, research by other groups and our previous finding suggests that CRT overexpression is a prevalent event in malignant transformation of esophageal epithelial cells (Nishimori et al, 2006;Du et al, 2007). Importantly, we observed that patients with CRT overexpression presented a shorter survival time compared to those with low CRT expression.…”
Section: Introductionsupporting
confidence: 57%
“…Our previous study identified 22 candidate proteins by proteomic analysis. Among them, we found that overexpression of Calreticulin (CRT) predicted a poor prognosis of ESCC patients (Du et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] More recently, the ALK gene has been shown to be involved in small subsets of epithelial malignancies, including carcinomas of pulmonary, esophageal, mammary gland, and gastrointestinal origin. [19][20][21][22] To the best of our knowledge, this is the first report of a recurrent ALK locus rearrangement in a primary kidney tumor. Although 2p23 chromosomal abnormalities have not been previously emphasized as recurrent in renal cell carcinoma, a review of the literature and search of the Mitelman database (http://www.ncbi.nlm.nih.gov/cancerchromosomes) yielded four additional primary renal carcinomas and one renal carcinoma cell line exhibiting karyotypic aberrations at or near the ALK gene 5,[33][34][35][36] (Table 4).…”
Section: Discussionmentioning
confidence: 71%
“…[19][20][21][22] The predicted structure and function of VCL-ALK oncoprotein follows the archetypical pattern defined by the combined properties of the N-terminal partner (ubiquitous expression and homopolymerization) and the C-terminal kinase domain (constitutive activation). On the basis of the current data, we propose that ALK fusion genes represent an oncogenic driver in a subset of renal cell carcinomas, and that recognition of these cases may be useful in ascertaining a patient's eligibility for emerging tyrosine kinase-targeted therapies, the clinical efficacy of which has been recently reported in a trial of ALK-positive non-small cell lung carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation